A high thermal conductivity graphite matrix material and its preparation method and application
By introducing auxiliary thermal conductivity fillers with a layered structure into the graphite powder, a complete thermal conductivity system is formed, which solves the problem of thermal stability and thermal conductivity of graphite materials under high temperature conditions, and significantly improves the heat dissipation performance and thermal stability of electronic devices.
Patent Information
- Application Number
- CN202311831725.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The thermal stability and thermal conductivity of existing graphite materials under high temperature conditions have decreased, resulting in poor heat dissipation performance of electronic components and shortened service life.
By introducing auxiliary thermal conductivity fillers with a layered structure into the graphite powder, a complete thermal conductivity and thermal stability of the graphite matrix material are improved.
It significantly improves the heat dissipation performance and thermal stability of electronic devices, and extends the service life of graphite matrix materials under high temperature conditions.
Smart Images

Figure CN117821028B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, in particular to a high thermal conductivity graphite matrix material and a preparation method and application of the high thermal conductivity graphite matrix material. Background Art
[0002] With the rapid development of science and technology, the increasing sophistication, integration and modularization of electronic components have led to a rapid increase in the heat accumulated by integrated circuit devices during operation, causing the operating temperature of electronic devices to be too high. Whenever the operating temperature of an integrated circuit device rises by 2°C, its overall stability will drop by one-tenth, and for every 6-8°C increase in the normal operating temperature of electronic devices such as motors, transformers, circuit boards and chips, the expected service life of electronic equipment will be sharply shortened, and may not reach half of the normal service life. Therefore, in order to enable electronic components to work stably and reliably, it is necessary to try to reduce the operating temperature of electronic components, that is, to improve the heat dissipation performance of electronic components as much as possible.
[0003] In the prior art, graphite materials with certain thermal conductivity are often used as thermal management materials to solve the heat dissipation problem of electronic components. However, graphite materials will produce defects under high temperature conditions, and their thermal stability and thermal conductivity will also decrease, which will shorten the service life of graphite materials under high temperature conditions and seriously affect the heat dissipation performance of electronic components.
[0004] Therefore, thermal management materials that can solve the heat dissipation problem of electronic components need to be further improved. Summary of the invention
[0005] In order to improve the above problems existing in the prior art, the present invention provides a high thermal conductivity graphite matrix material, a preparation method of the high thermal conductivity graphite matrix material, and the application of the high thermal conductivity graphite matrix material in electronic devices. The high thermal conductivity graphite matrix material of the present invention has high thermal conductivity and thermal stability in a high temperature environment, so that the heat dissipation performance of the electronic device using the material is significantly improved.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a high thermal conductivity graphite matrix material, wherein the high thermal conductivity graphite matrix material comprises graphite powder and an auxiliary thermal conductive filler, wherein the auxiliary thermal conductive filler is a layered material that can form a complete thermal conductive system with the graphite powder; relative to 100 parts by weight of the graphite powder, the content of the auxiliary thermal conductive filler is 1-8 parts by weight.
[0007] The second aspect of the present invention provides a method for preparing the high thermal conductivity graphite matrix material of the first aspect of the present invention, the method comprising the following steps:
[0008] (1) subjecting expanded graphite to oxidation treatment and freeze drying treatment;
[0009] (2) modifying the material obtained in step (1) using the modifier to obtain an auxiliary thermal conductive filler;
[0010] (3) Mixing the material obtained in step (2) with the graphite powder, and subjecting the mixture to static pressing to obtain the high thermal conductivity graphite matrix material.
[0011] The third aspect of the present invention provides the use of the high thermal conductivity graphite matrix material described in the first aspect of the present invention or the high thermal conductivity graphite matrix material prepared in the second aspect of the present invention in electronic devices.
[0012] Through the above technical scheme, the present invention has at least the following advantages compared with the prior art: the present invention introduces a layered auxiliary thermal conductive filler into the graphite powder that can form a complete thermal conductive system with the graphite powder, thereby improving the thermal conductivity of the graphite powder in a high temperature environment, thereby improving the thermal conductivity and thermal life of the graphite matrix material, and thus significantly improving the heat dissipation performance of electronic devices.
[0013] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a SEM image of graphene oxide before and after modification provided by one embodiment of the present invention.
[0015] Figure 2 FT-IR images of graphene oxide before and after modification provided by one embodiment of the present invention. DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0017] At present, thermal management composite materials on the market often improve the dielectric, mechanical and thermal properties of thermal management composite materials by introducing high-performance inorganic fillers into the matrix. However, few people pay attention to how to better achieve heat dissipation management of graphite matrix materials, further improve thermal conductivity, and form a more complete, regular and efficient thermal conductive system. Therefore, the inventors of the present invention have obtained a solution to improve the heat dissipation performance of graphite matrix materials in electronic devices after in-depth research.
[0018] The first aspect of the present invention provides a high thermal conductivity graphite matrix material, the high thermal conductivity graphite matrix material includes graphite powder and auxiliary thermal conductive filler, the auxiliary thermal conductive filler is a material that can form a complete thermal conductive system with the graphite powder; relative to 100 parts by weight of the graphite powder, the content of the auxiliary thermal conductive filler is 1-8 parts by weight. It can be understood that the present invention can make the interlayer spacing between graphite flakes in the graphite powder tend to be stable under high temperature environment by introducing an appropriate amount of auxiliary thermal conductive material into the graphite powder, and because the auxiliary thermal conductive material has a special layered structure, it can form a complete thermal conductive system with the graphite powder, thereby improving the thermal conductivity of the graphite powder itself.
[0019] It should be noted that the interlayer spacing between graphite sheets will affect the heat transfer impedance between sheets. The smaller the interlayer spacing, the smaller the heat transfer impedance between sheets, and the better the thermal conductivity of the graphite powder itself. When the graphite powder is in a high temperature environment, the interaction between the layers is weak, and the interlayer spacing will increase, because the weak interaction force reduces the attraction or repulsion between adjacent layers, making them easier to separate or slide from each other. The increase in interlayer spacing may cause the stability of the layered structure of the graphite powder to decrease, and even delamination may occur, thereby generating more pores and defects, resulting in a loose structure and affecting the thermal conductivity of the graphite powder. The introduction of auxiliary thermal conductive materials can enhance the interaction between layers, making the layers more densely bonded, and the special layered auxiliary thermal conductive materials can form a composite material with graphite powder materials that has a high stability and a complete thermal conductive system, thereby effectively improving the thermal conductivity and thermal life of the graphite matrix material in a high temperature environment, and significantly improving the heat dissipation performance and thermal stability of electronic devices.
[0020] In the present invention, the term "interlayer spacing" refers to the distance between each mesh layer of layered graphite crystals bonded by van der Waals forces. The interlayer spacing between graphite crystal sheets is a key factor affecting the thermal conductivity of graphite powder materials. The increase in the interlayer spacing between graphite crystal sheets will increase the distance of heat transfer inside the graphite crystals, which will lead to relatively low thermal conductivity of graphite powder materials. This is also the reason why actual graphite powder materials will have thermal conductivity defects under high temperature conditions. Therefore, the present invention can make the interlayer spacing between graphite sheets in the graphite powder stable under high temperature conditions by introducing an appropriate amount of auxiliary thermal conductive materials, thereby extending its service life under high temperature conditions and effectively improving the thermal conductivity of graphite powder.
[0021] In the present invention, relative to 100 parts by weight of the graphite powder, the content of the auxiliary thermally conductive filler is 1-8 parts by weight. In one example, relative to 100 parts by weight of the graphite powder, the content of the auxiliary thermally conductive filler can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight or a range consisting of any two numerical values. By matching the graphite powder with the specific auxiliary thermally conductive material in a specific ratio, the stability of the distance between the graphite crystal sheets in the graphite powder can be further improved, and a layered thermally conductive system with better stability is formed, further improving the thermal conductivity of the graphite powder. In one example, relative to 100 parts by weight of the graphite powder, the content of the auxiliary thermally conductive filler is 1-6 parts by weight, more preferably 2-5 parts by weight.
[0022] In one example, the auxiliary thermal conductive filler is graphene powder, and the auxiliary thermal conductive filler contains a first oxygen-containing polar functional group; the first oxygen-containing polar functional group is selected from one or more of hydroxyl, carboxyl, carbonyl, keto and epoxy groups. Graphene material is a carbon-based material with excellent performance and low cost, and has good mechanical properties and chemical stability. When graphene powder is used as a filler in a graphite matrix material system, due to its special layered structure, it can interact with the layered structure of graphite crystals to form a complete layered conductive system, thereby effectively improving the thermal conductivity defects of the graphite matrix material, improving the thermal conductivity, thermal stability and chemical stability of the graphite powder material, and also improving the mechanical properties of the graphite powder substrate. Furthermore, the auxiliary thermally conductive filler also contains abundant first oxygen-containing polar functional groups, which can further enhance the interfacial interaction force between the interface layer of the auxiliary thermally conductive filler and the graphite crystal lamellar structure inside the graphite powder, so that the cross-linking between the auxiliary thermally conductive filler and the lamellar structure inside the graphite powder is more stable, thereby forming a composite material with a complete thermal conductive system, thereby effectively improving the thermal conductivity of the graphite matrix material.
[0023] In order to form a more regular conductive system between the graphene oxide sheets and the lamellar structure of graphite crystals in the graphite powder, further enhance the interfacial force between the lamellar structures, and further enhance the dispersion performance of the graphene oxide sheets between graphite powders. In one example, the auxiliary thermal conductive filler also contains a second oxygen-containing polar functional group, which is formed by a bonding reaction between the modifier and the first oxygen-containing polar functional group. It is understandable that the degree of dispersion of graphene oxide sheets between graphite powders will directly affect the effect of graphene oxide on improving the thermal conductivity of graphite powders. By introducing the second oxygen-containing polar functional group into the auxiliary thermal conductive filler, it is possible to avoid bonding between the first oxygen-containing polar functional groups caused by the excessive density of the first oxygen-containing polar functional group in some areas, thereby affecting the improvement of the interfacial force between the lamellar structures.
[0024] It should be noted that the bonding reaction between the modifier and the first oxygen-containing polar functional group refers to the reaction in which the oxygen atom of the oxygen-containing polar group (such as hydroxyl, carboxyl, carbonyl, keto or epoxy) in the first oxygen-containing polar functional group forms a covalent bond with the silicon atom in the modifier, and is also a reaction in which some groups in the oxygen-containing polar group are replaced.
[0025] In order to further improve the dispersibility of graphene oxide sheets among graphite powders, in one example, the degree of substitution of the second oxygen-containing polar functional group is 70%-90%. It should be noted that the degree of substitution of the second oxygen-containing polar functional group refers to the number of groups of the first oxygen-containing polar functional group replaced by the second oxygen-containing polar functional group (the number of substitutions of the second oxygen-containing polar functional group) / the total number of the first oxygen-containing polar functional group before modification (the total number of the first oxygen-containing polar functional group and the second oxygen-containing polar functional group after modification). It is understandable that when the degree of substitution of the second oxygen-containing polar functional group is less than 70%, the number of groups of the first oxygen-containing polar functional group is too large, and bonding between the first oxygen-containing polar functional groups is easy to occur, which will affect the improvement of the interfacial force between the lamellar structures. When the degree of substitution of the second oxygen-containing polar functional group is greater than 90%, the number of groups of the second oxygen-containing polar functional group is too large, which weakens the interfacial force between the lamellar structures and affects the thermal conductivity of the graphite material. In addition, in the actual substitution process, the degree of substitution of the second oxygen-containing polar functional group is generally difficult to reach more than 90%. In one example, the degree of substitution of the second oxygen-containing polar functional group can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%. Further limiting the degree of substitution of the second oxygen-containing polar functional group can more accurately control the number of the two oxygen-containing polar functional groups, thereby maintaining the interfacial forces between the sheet structures while ensuring the dispersion performance of the graphene oxide sheets between the graphite powders. In one example, the degree of substitution of the graphene oxide is 82%-90%.
[0026] In one example, the modifier is selected from one or both of γ-glycidyloxypropyltrimethoxysilane (K560) and γ-aminopropyltriethoxysilane (K550). It should be noted that the use of oxygen-functionalized silane coupling agent as a modifier can modify the surface of the auxiliary thermal conductive filler graphene oxide, and can form a more regular conductive system between the graphene oxide sheet and the lamellar structure of graphite crystals in the graphite powder, which can further enhance the interfacial force between the lamellar structure and the dispersion performance of the graphene oxide sheet between the graphite powder.
[0027] In the present invention, the high thermal conductivity graphite matrix material may also include a small molecule compound, which is equivalent to 100 parts by weight of the graphite powder, and the content of the small molecule compound is 0.1-10 parts by weight. In one example, the content of the small molecule compound equivalent to 100 parts by weight of the graphite powder can be 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight. In one example, the content of the polymer material is 1-6 parts by weight, which is equivalent to 100 parts by weight of the graphite powder. In one example, the small molecule compound is selected from one or more of boric acid, phenylboron, acid fluorine sugar, fluoroether alcohol, aminoketone, and p-nitrophenol. It can be understood that by adding one or more of the above-mentioned small molecule compounds to the high thermal conductivity graphite matrix material and controlling the appropriate weight ratio, a certain amount of B, F, and N source materials can be doped into the high thermal conductivity graphite matrix material, which can further improve the thermal conductivity of the graphite matrix.
[0028] The high thermal conductivity graphite matrix material of the present invention may also contain other conventional components in the art, which may be added to the present invention according to the needs of those skilled in the art as long as they do not inhibit the performance of the main components.
[0029] The second aspect of the present invention provides a method for preparing the high thermal conductivity graphite matrix material of the first aspect of the present invention, the method comprising the following steps:
[0030] (1) subjecting expanded graphite to oxidation treatment and freeze drying treatment;
[0031] (2) modifying the material obtained in step (1) using the modifier to obtain an auxiliary thermal conductive filler;
[0032] (3) Mixing the material obtained in step (2) with the graphite powder, and subjecting the mixture to static pressing to obtain the high thermal conductivity graphite matrix material.
[0033] In step (1), the specific method and steps of oxidizing the expanded graphite are as follows: Step 1, low temperature reaction stage, add expanded graphite, concentrated sulfuric acid and fuming nitric acid into a reaction container and mix, and place the reaction container in an ice water bath and continue stirring for 1-3 hours; Step 2, temperature rise reaction stage, remove the ice water bath, place the reaction container in a 20-50°C water bath and continue stirring for 2-5 hours, then heat to 80-100°C and react for 1-3 hours; Step 3, purification stage, add 10-40% hydrogen peroxide solution into the reaction container until no more bubbles are generated in the reaction container. At this time, the reactant after the oxidation treatment is bright yellow.
[0034] In step (1), after the oxidation treatment and before the freeze-drying treatment, dialysis treatment and centrifugation treatment are also included. The specific methods and steps of the dialysis treatment and the centrifugation treatment are as follows: Step 1, dialysis treatment, deionized water is added to the reactant after the oxidation treatment to dilute it into a solution, and then the solution is placed in a dialysis bag for dialysis, and the deionized water is replaced until the dialyzed pH value is close to 7; Step 2, centrifugation treatment, the dialyzed product is centrifuged with deionized water at a centrifugal speed of 2000-10000r / min for 5-20min to obtain a product.
[0035] In step (1), the freeze-drying treatment conditions include: temperature of -10°C to 0°C, time of 12h to 48h. The specific operation is: placing the product obtained by centrifugation in a freeze-drying machine, freeze-drying it in a low temperature environment for 12-48h, and finally grinding it fully to obtain graphene oxide powder.
[0036] In step (2), the material obtained in the above step (1) is modified using a modifier, and the specific method and steps are as follows: the material powder obtained in the above step (1) and 2-10wt% of the modifier accounting for the total weight of the material powder are added to a reaction container, ultrasonically stirred for 1-4 hours, and then heated at 60-100°C for 1-4 hours; after heating, centrifugal treatment is performed at a centrifugal speed of 2000-10000r / min and a centrifugal time of 2-15min; then drying and grinding are performed to finally obtain the auxiliary conductive filler powder.
[0037] In step (3), the static pressing molding process adopts cold isostatic pressing technology, and the conditions of the static pressing molding process include: pressure of 100MPa-400MPa, temperature of 100℃-500℃, and time of 8h-18h. Specifically, the specific steps and methods of the cold isostatic pressing technology of the static pressing molding process in step (3) are as follows: the auxiliary conductive filler powder obtained in step (2) is pressed and filled into a rubber mold, and the pressed powder is compacted by high-frequency electromagnetic vibration. After sealing, vacuum is evacuated to exhaust the air between the powder particles, and the auxiliary conductive filler powder is placed in a high-pressure container filled with a liquid medium such as water or oil, and the pressure is increased to 100MPa-400MPa. The auxiliary conductive filler powder is pressed into a cylindrical or rectangular high thermal conductivity graphite matrix material product. It should be noted that, according to Pascal's principle, pressure is applied to the rubber mold through liquid media such as water, and the pressure in all directions is equal. When the powder is compressed by the above-mentioned cold isostatic pressing technology, the pressed powder particles are not compressed in the filling direction in the mold, but are compressed in an irregular arrangement. Therefore, although the graphite matrix material is anisotropic in its crystallographic properties, on the whole, the isostatically pressed graphite matrix material is close to isotropic, so that the thermal conductivity of the final graphite matrix material product is more stably improved and suitable for various application fields.
[0038] The high thermal conductivity graphite matrix material of the present invention can be obtained by the above method. It should be noted that the deformation and replacement steps in the above steps that can be performed by those skilled in the art also belong to the protection scope of the present invention.
[0039] The third aspect of the present invention provides the application of the high thermal conductivity graphite matrix material described in the first aspect of the present invention and / or the high thermal conductivity graphite matrix material prepared in the second aspect of the present invention in electronic devices. Specifically, the high thermal conductivity graphite matrix material can be used as a thermal management material to improve the heat dissipation performance of electronic devices, and can be used in any related electronic components, such as: electronic equipment devices such as batteries, motors, transformers, circuit boards, or electronic components in the field of semiconductor chips and integrated circuits.
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] Used for the preparation of high thermal conductivity graphite matrix materials.
[0043] (1) Preparation of graphene oxide
[0044] Low temperature reaction stage: put expanded graphite (1g) in the middle port of the three-necked flask (500mL) in the reaction vessel, and slowly add concentrated sulfuric acid (75ml) and fuming nitric acid (25ml) solutions from the other port; after the graphite is completely settled, place the three-necked flask in an ice water bath and stir mechanically for 60min; then add potassium permanganate powder (6g) from the other port where no material has been added every 10min; after adding potassium permanganate, continue to stir mechanically for 1h in the ice water bath;
[0045] Temperature reaction stage: remove the ice water bath, place the reaction vessel in a 35°C water bath and continue mechanical stirring for 3 hours; after stirring, add deionized water to the reaction vessel; when the water bath temperature slowly rises to 98°C, continue mechanical stirring for 1 hour, at which time the solution color becomes yellow-brown;
[0046] Purification stage: Continue to slowly add 30% H2O2 solution to remove excess potassium permanganate powder and newly generated MnO2 in the solution until no bubbles are generated in the reaction vessel and the solution color becomes bright yellow;
[0047] Then, dialysis and centrifugation treatment are performed, deionized water is added to the above-mentioned oxidation-treated reactant to dilute it to prepare a solution, and then the solution is placed in a dialysis bag for dialysis, and the deionized water is replaced until the dialyzed pH value is close to 7; then the above-mentioned dialyzed product is centrifuged with deionized water at a centrifugal speed of 10000r / min for 8 minutes;
[0048] Finally, freeze drying was performed, and the product after centrifugation was placed in a freeze dryer and freeze dried for 24 hours at a low temperature of -5°C, and fully ground to obtain graphene oxide powder.
[0049] (2) Modification of graphene oxide
[0050] The graphene oxide powder (0.5 g) obtained in step (1) and deionized water (100 ml) were added to a three-necked flask, and then 5 wt% of γ-glycidyloxypropyltrimethoxysilane (K560) was added for modification, and then ultrasonicated and stirred for 2 h, and the device was moved to a water bath, and heated in a water bath at 80° C. for condensation and reflux for 3 h. After the heating was completed, the powder was centrifuged at a speed of 8000 r / min for 5 min, dried and ground, and finally the graphene oxide powder modified by the modifier was obtained, i.e., the auxiliary thermal conductive filler, and the degree of substitution of the second oxygen-containing polar functional group of the auxiliary thermal conductive filler was 86%.
[0051] (3) Preparation of graphite matrix materials
[0052] 100 parts by weight of graphite powder and 2 parts by weight of the auxiliary thermal conductive filler obtained in the above step (2) are mixed and fully ground, and then subjected to a cold isostatic pressing process to form the graphite matrix material of this embodiment.
[0053] Among them, the scanning electron microscope images of graphene oxide before and after modification in step (2) are as follows Figure 1 As shown, Figure 1 Figure a) is a microscopic morphology of unmodified graphene oxide, from which it can be clearly seen that the structure of graphene oxide is a two-dimensional lamellar structure. Since the microstructure of graphene oxide contains a large number of oxygen-containing polar functional groups, such as hydroxyl groups and carboxyl groups, it is easy to form hydrogen bonds between the lamellar layers, resulting in a more obvious overlap between the lamellar layers of graphene oxide. Figure 1 Figure b) shows graphene oxide modified with γ-glycidyloxypropyltrimethoxysilane. Comparison of the two figures shows that the grafting of the modified coupling agent greatly reduces the hydrogen bonds in the graphene oxide structure, causing its lamellar structure to peel off, and the overall molecular chain becomes longer, which is more conducive to dispersion. The remaining polar groups such as carboxyl and carbonyl in the structure can also give graphene oxide a strong hydrophilicity, thereby effectively improving the dispersion of graphene oxide.
[0054] In addition, the FT-IR images of graphene oxide before and after modification in step (2) are as follows: Figure 2 As shown, Figure 2 Curve (a) in is the FT-IR graph of unmodified graphene oxide. Figure 2 Curve (b) in the figure is the FT-IR graph of graphene oxide modified with γ-glycidyloxypropyltrimethoxysilane. -1 and 1089cm -1 The absorption peak at 1610 cm -1 The stretching vibration of C=O is located at 1404 cm -1 The absorption peak at 1248 cm corresponds to the deformation vibration of -OH in -COOH. -1 The characteristic diffraction peaks at 1000 cm-1 correspond to the symmetrical stretching vibration of the epoxy group. The existence of these diffraction peaks fully proves that a large number of oxygen-containing functional groups are introduced in the step (1) of the experimental preparation. Compared with the infrared spectrum of unmodified graphene oxide, the modified graphene oxide (curve b) is located at 1000 cm-1. -1 Up to 1500cm -1 The absorption peak of oxygen-containing groups in the wave number basically disappeared, indicating that the modifier and graphene oxide had a bonding reaction, resulting in a large reduction of oxygen-containing groups in the graphene oxide structure. At the same time, a new characteristic diffraction peak was added, located at 1078cm -1The absorption peak at corresponds to the stretching vibration of the Si-O bond. The existence of the silicon-oxygen bond indicates that the silicon atoms in the modified coupling agent have been successfully grafted onto GO. The existence of this characteristic peak proves that the modifier has successfully modified graphene oxide.
[0055] Example 2 Group
[0056] Example 2 was carried out with reference to Example 1, except that the amount of auxiliary thermal conductive filler added was changed, as follows:
[0057] Example 2-1, the weight of the auxiliary thermal conductive filler is changed from 2 weight parts to 1 weight part;
[0058] Example 2-2, the weight of the auxiliary thermal conductive filler is changed from 2 parts by weight to 4 parts by weight;
[0059] Example 2-3, the weight of the auxiliary thermal conductive filler is changed from 2 parts by weight to 5 parts by weight;
[0060] In Example 2-4, the weight of the auxiliary thermal conductive filler is changed from 2 parts by weight to 6 parts by weight;
[0061] In Example 2-5, the weight of the auxiliary thermal conductive filler is changed from 2 parts by weight to 8 parts by weight.
[0062] Example 3
[0063] Example 3 is used to illustrate the situation when different auxiliary heat-conducting materials are used.
[0064] Example 3 was carried out with reference to Example 1, except that graphene oxide powder modified with γ-aminopropyltriethoxysilane (K550) was used as the auxiliary thermal conductive material.
[0065] Example 4
[0066] Example 4 is used to illustrate the situation when the degree of substitution of the second oxygen-containing polar functional group of the auxiliary thermally conductive filler is changed.
[0067] Example 4 was carried out with reference to Example 1, except that the amount of the modifier γ-glycidyloxypropyltrimethoxysilane (K560) added was reduced so that the degree of substitution of the second oxygen-containing polar functional group of the auxiliary thermal conductive filler was 75%.
[0068] Comparative Example 1
[0069] Comparative Example 1 was carried out with reference to Example 1, except that the graphite matrix material did not contain auxiliary conductive filler.
[0070] Comparative Example 2
[0071] Comparative Example 2 was carried out with reference to Example 1, except that the weight of the auxiliary conductive filler was changed from 2 parts by weight to 0.5 parts by weight.
[0072] Comparative Example 3
[0073] Comparative Example 3 was carried out with reference to Example 1, except that the weight of the auxiliary conductive filler was changed from 2 parts by weight to 10 parts by weight.
[0074] Comparative Example 4
[0075] Comparative Example 4 was carried out with reference to Example 1, except that the amount of the modifier γ-glycidyloxypropyltrimethoxysilane (K560) added was reduced, so that the degree of substitution of the second oxygen-containing polar functional group of the auxiliary thermal conductive filler was 43%.
[0076] Test Case
[0077] Thermal conductivity test
[0078] The graphite matrix materials obtained in the above embodiments and comparative examples were subjected to thermal conductivity testing under a test environment of 100°C (200°C or 300°C), wherein the thermal conductivity testing instrument was the American TA lfa1600, and the temperature parameters were set to: heating rate 5°C / min; the specific steps were as follows: prepare the sample: select a suitable sample and ensure that its size and shape meet the test requirements; install the sample: install the sample in the test device to ensure that it is in good contact with the heat source and the temperature sensor; set the heat source: set a suitable heat source to provide an instantaneous heat pulse; measure the temperature change: measure the temperature change of the sample under the action of the heat pulse; calculate the thermal conductivity: according to the measured temperature change and the known heat source parameters, use an appropriate formula to calculate the thermal conductivity (unit W / (m·K)) of the above material, and record the specific results in Table 1.
[0079] Table 1
[0080]
[0081] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A high thermal conductivity graphite matrix material, characterized in that: It comprises graphite powder and auxiliary thermal conductive filler, wherein the auxiliary thermal conductive filler is a layered material capable of forming a complete thermal conductive system with the graphite powder; the content of the auxiliary thermal conductive filler is 1-6 parts by weight relative to 100 parts by weight of the graphite powder; The auxiliary thermal conductive filler is graphene powder, and the auxiliary thermal conductive filler contains a first oxygen-containing polar functional group; the first oxygen-containing polar functional group is selected from one or more of a hydroxyl group, a carboxyl group, a carbonyl group, a keto group and an epoxy group; The auxiliary thermal conductive filler also contains a second oxygen-containing polar functional group, which is formed by a bonding reaction between a modifier and the first oxygen-containing polar functional group; the degree of substitution of the second oxygen-containing polar functional group is 70%-90%; the modifier is selected from one or both of γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
2. The high thermal conductivity graphite matrix material according to claim 1, characterized in that: The high thermal conductivity graphite matrix material also includes a small molecule compound, which is equivalent to 100 parts by weight of the graphite powder, and the content of the small molecule compound is 0.1-10 parts by weight; The small molecule compound is selected from one or more of boric acid, phenylboron, acid fluorosugar, fluoroether alcohol, aminoketone and p-nitrophenol.
3. A method for preparing the high thermal conductivity graphite matrix material according to claim 1, characterized in that: The method comprises the following steps: (1) subjecting the expanded graphite to oxidation treatment and freeze drying treatment; (2) modifying the material obtained in step (1) using the modifier to obtain the auxiliary thermal conductive filler; (3) The material obtained in step (2) is mixed with the graphite powder, and subjected to static pressing to obtain the high thermal conductivity graphite matrix material.
4. The method according to claim 3, characterized in that In step (1), the freeze-drying process also includes dialysis and centrifugation before the freeze-drying process; And / or, in step (1), the freeze-drying treatment conditions include: temperature of -10°C to 0°C, and time of 12h to 48h.
5. The method according to claim 3, characterized in that: In step (3), the isostatic pressing process adopts cold isostatic pressing technology, and the conditions of the isostatic pressing process include: pressure of 100MPa-400MPa, temperature of 100°C-500°C, and time of 8h-18h.
6. Use of the high thermal conductivity graphite matrix material according to any one of claims 1 to 2 or the high thermal conductivity graphite matrix material prepared by the method according to claims 3 to 5 in electronic devices.
Citation Information
Patent Citations
Heat conduction material and preparation method and application thereof
CN106977909A
Preparation method of graphene heat-conducting composite material
CN106987236A
Preparation method of graphene / graphite powder composite material, composite material and application
CN107022345A
Silicone rubber high-heat-conducting material
CN112080149A